Monetary policy and inflation modeling in a more open economy in South Africa - Aron, J; Muellbauer, J (University of Oxford, 2008)
South Africa in the 1990s became globally more integrated after years of isolation. Opening the trade and capital accounts gave impetus to a monetary policy regime change to inflation targeting from 2000, after a costly transitional period of monetary mismanagement with low policy transparency. Changes in openness can, however, disrupt the inflation forecasting on which targeting monetary policies depend. This chapter demonstrates how the central bank's own producer price inflation equation in its core model can be improved by taking account of greater openness, using both innovative time-series openness measures and a more conventional measure. The model has a greatly improved fit and stability over longer samples when also including the real exchange rate and the interest rate differential (making explicit the exchange rate channel of monetary transmission) and asymmetric food price inflation. Moreover, there is a role for the level of the output gap rather than simply a short-run effect, as in the central bank's model. This helps mitigate the arguments in current South African debate regarding the apparent unconcern of inflation targeting policy for the level of economic activity.